2022
DOI: 10.7759/cureus.22604
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Awareness and Perception of Children’s Eye Diseases in Madinah, Saudi Arabia: A Cross-Sectional Study

Abstract: BackgroundThe visual system becomes more susceptible to conditions causing abnormal binocular interaction or blurred visual input as it matures during the first six years of life. Therefore, detection and treatment of visual impairment at a young age can lower the burden of the condition in adulthood. According to estimates, there are 19 million children worldwide with visual impairment, and 1.4 million children suffer from blindness. One of the strategies to address blinding eye conditions and visual impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…In this self-reported cross-sectional study, we aimed to assess parents' awareness and attitude toward pediatric eye diseases. A previous study reported poor knowledge in 78.2% of parents [ 7 ], whereas another study reported poor knowledge among 91.9% of parents [ 8 ]. Consistently, our findings showed that 72.8% of parents had a low level of awareness regarding pediatric eye diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this self-reported cross-sectional study, we aimed to assess parents' awareness and attitude toward pediatric eye diseases. A previous study reported poor knowledge in 78.2% of parents [ 7 ], whereas another study reported poor knowledge among 91.9% of parents [ 8 ]. Consistently, our findings showed that 72.8% of parents had a low level of awareness regarding pediatric eye diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the previous studies regarding this subject reveal the need for further assessment of the knowledge about children's eye diseases among parents and its associated factors to enhance the improvement of their understanding level [ 7 , 8 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The preferred source of information about cross-eye was doctors or healthcare workers for most of the responders. Relatives and friends represented the main source of knowledge about strabismus in some studies [ 14 , 19 ], while in other studies the reported resources were doctors, internet browsers, and social media [ 29 , 30 ]. Unsurprisingly, the internet and social media use to obtain information about strabismus was the least among participants.…”
Section: Discussionmentioning
confidence: 99%